Preparation method of bio-based spherical porous carbon, preparation method of bio-based spherical silicon-carbon negative electrode material and battery

Bio-based spherical porous carbon is prepared by sol-gel method, and silicon vapor deposition and carbon vapor coating are carried out on it, solving the problems of unsatisfactory porous carbon channel structure and poor fluidity in the prior art, achieving high-performance preparation of bio-based spherical silicon carbon negative electrode materials, and improving the cycle life and resistivity of the battery.

CN119750575AActive Publication Date: 2025-04-04SHANDONG SHENGQUAN NEW ENERGY TECH CO LTD

Patent Information

Application Number
CN202411930247.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-04-04
Estimated Expiration
2044-12-25

AI Technical Summary

Technical Problem

During the preparation process, the existing new silicon carbon anode materials have problems such as unsatisfactory porous carbon pore structure, poor fluidity, floating silicon problems, and poor cycle life. The preparation process is complicated and the product performance is poor.

Method used

Bio-based spherical porous carbon was prepared by sol-gel method. By adding crosslinking agent and dispersant to the papermaking black liquid, drying, dehydrating, alkali-activated pore formation and gas-phase deaeration, bio-based spherical porous carbon was obtained with uniform pore size and good fluidity, and on the basis of it, silicon vapor deposition and carbon vapor coating were carried out to prepare a bio-based spherical silicon carbon negative electrode material.

Benefits of technology

The structural strength and pore consistency of porous carbon are improved, the resistivity of silicon carbon negative electrode materials and the restriction ability of silicon-embedded lithium expansion are enhanced, the cycle life of the battery is extended, and the powder resistivity is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119750575A_ABST
    Figure CN119750575A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of bio-based spherical porous carbon, a preparation method of a bio-based spherical silicon-carbon negative electrode material and a battery. The preparation method of the bio-based spherical porous carbon comprises the following steps: synthesizing a precursor; drying and dehydrating; an alkali activation pore-forming step; and a gas-phase deliming step. The preparation method of the bio-based spherical silicon-carbon negative electrode material further comprises the steps of carrying out silicon vapor deposition and carbon vapor coating on the bio-based spherical porous carbon. Through the preparation method of the bio-based spherical porous carbon, the bio-based spherical porous carbon with the characteristics of proper pore size, uniform pore size, regular sphere (good fluidity), single particle strength and the like can be obtained; the bio-based spherical silicon-carbon negative electrode material obtained by the preparation method of the bio-based spherical silicon-carbon negative electrode material has the excellent effects of lower resistivity, higher limiting capability of lithium-embedded expansion of internal silicon and the like, so that the bio-based spherical silicon-carbon negative electrode material can be used for obtaining a battery with better performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the field of biomass refining and comprehensive utilization, and specifically relates to a method for preparing bio-based spherical porous carbon, a method for preparing bio-based spherical silicon-carbon negative electrode material, and a battery. Background Art

[0002] Most of the existing new silicon-carbon negative electrode materials use porous carbon as the substrate. Vapor deposition is carried out in an atmosphere containing a silicon source to deposit nanosilicon into the pores of the porous carbon. Then, vapor coating is carried out in an atmosphere containing a carbon source to wrap a layer of carbon on the surface of the material. The resulting silicon-carbon composite material can be used as a battery negative electrode material to achieve high capacity and long cycle life, while effectively improving the high expansion and low rate shortcomings of silicon-based negative electrode materials.

[0003] This new type of silicon-carbon material requires nano-silicon to be deposited into the pores of porous carbon. On the one hand, the pore structure of porous carbon needs to have good adsorption capacity for silicon source gas to ensure that the reaction process of silicon source gas cracking into nano-silicon occurs inside the porous carbon pores. This places high demands on the structural parameters of porous carbon. If the structure of porous carbon is not ideal, silicon will be deposited on the surface of the material, resulting in floating silicon, which will lead to deterioration of material processing performance and cycle life. On the other hand, silicon-containing source gas needs to have sufficient gas-solid contact with porous carbon, which places high demands on the fluidity of porous carbon materials. If the material fluidity is poor, it is easy to agglomerate and clump in the equipment, resulting in uneven reaction during silicon vapor deposition and carbon vapor coating, and poor product performance.

[0004] At present, coconut shell carbon and resin are mostly used as precursors in the preparation of porous carbon, and the activation methods include steam activation, CO 2 Activation and alkali activation. The equipment used for activation includes roller kilns, rotary kilns and other kilns. Porous carbon prepared by different processes has different disadvantages. For example, the porous carbon prepared by coconut shell charcoal has low structural strength and poor pore structure consistency. The prepared new silicon-carbon negative electrode has high expansion rate and poor electrochemical performance. The raw material cost of resin-based activated carbon is high. Water vapor, CO 2 The pore structure of activated pore making is uncontrollable, which will lead to poor cycle performance of the prepared new silicon-carbon negative electrode. The alkaline activated pore making process is complicated, the product ash content is high, and the wastewater is difficult to treat.

[0005] Since silicon vapor deposition and carbon vapor coating need to be carried out at a certain gas flow rate, there are strict requirements on the particle size distribution of porous carbon. If the Dv10 of the porous carbon is too low and there are more small-particle fine powders, it will significantly affect the effects of silicon deposition and carbon coating, resulting in poor product performance. Therefore, after the porous carbon is prepared and before silicon vapor deposition, the porous carbon needs to be crushed and graded. Summary of the invention

[0006] In order to solve the problems in the prior art, the present application provides a method for preparing bio-based spherical porous carbon, a method for preparing a bio-based spherical silicon-carbon negative electrode material from the above bio-based spherical porous carbon, and a battery prepared from the above bio-based spherical silicon-carbon negative electrode material. The technical solution of the present application is as follows:

[0007] 1. A method for preparing bio-based spherical porous carbon, comprising:

[0008] Precursor synthesis step: adding a crosslinking agent and a dispersant to papermaking black liquor, and preparing a slurry containing bio-based microspheres by a sol-gel method, wherein the papermaking black liquor is papermaking black liquor produced by alkaline papermaking;

[0009] Drying and dehydrating step: drying and dehydrating the slurry under a protective atmosphere to obtain dried and dehydrated bio-based microspheres;

[0010] Alkali activation pore-forming step: in a protective atmosphere and at an activation temperature, the dried and dehydrated bio-based microspheres are subjected to alkali activation using the alkaline pore-forming agent that is rich in the microspheres;

[0011] Gas phase deashing step: adding acidic gas under protective atmosphere, so that the acidic gas and impurities generate salt and are gasified and removed to obtain the bio-based spherical porous carbon.

[0012] 2. The preparation method according to item 1, wherein:

[0013] The solid content of the papermaking black liquor is 30% to 60%;

[0014] The pH of the papermaking black liquor is ≥ 11.0, preferably ≥ 12.0; and / or,

[0015] The Na content of the papermaking black liquor is between 200,000 and 400,000 ppm, preferably between 230,000 and 250,000 ppm.

[0016] 3. The preparation method as described in item 1, wherein:

[0017] The cross-linking agent is selected from any one of toluene, phenol, resorcinol, formaldehyde, paraformaldehyde, hexamethylenetetramine, and azobisisobutyl cyanide, or a combination of two or more thereof; preferably, the mass of the cross-linking agent added is 1 to 20% of the mass of the papermaking black liquor; and / or,

[0018] The dispersant is selected from one or a combination of two or more of gelatin, polyvinyl alcohol, polyethylene glycol, white oil, polyvinyl pyrrolidone, sodium polyacrylate, and sorbitan oleate; preferably, the mass of the dispersant added is 0.1-20% of the mass of papermaking black liquor.

[0019] 4. The preparation method according to item 1, wherein:

[0020] The precursor synthesis step is carried out in a closed reactor; the heating temperature is 170-190° C., preferably 175-185° C.; the heating time is ≥18 h, preferably 22-24 h.

[0021] 5. The preparation method according to item 1, wherein:

[0022] The drying and dehydration step is carried out in an activated fluidized bed; the drying and dehydration step includes a drying sub-step and a dehydration sub-step carried out after the drying sub-step; wherein,

[0023] In the drying sub-step, the slurry is sprayed into the activated fluidized bed through a two-fluid atomizing nozzle under a protective atmosphere; the drying temperature is 100-150° C., preferably 110-120° C.; the drying time after the slurry is completely in the activated fluidized bed is 0.5-6 hours;

[0024] The dehydration temperature of the dehydration sub-step is 200-800° C., preferably 300-600° C.; the dehydration time is 0.5-6 hours.

[0025] 6. The preparation method according to item 1, wherein:

[0026] The alkali-activated pore-forming step is carried out in an activated fluidized bed;

[0027] The activation temperature is 600-1100°C, preferably 750-950°C;

[0028] The activation time is 0.5 to 24 hours.

[0029] 7. The preparation method according to item 6, wherein:

[0030] In the alkali-activated pore-forming step, the inert gas of the protective atmosphere is continuously introduced from the bottom of the gas-activated fluidized bed.

[0031] 8. The preparation method according to item 1, wherein:

[0032] The gas phase deashing step is carried out in an activated fluidized bed;

[0033] The gas phase deashing temperature is 400-1100°C, preferably 650-950°C;

[0034] The decalcification time is 0.5 to 6 hours.

[0035] 9. The preparation method according to item 1, wherein:

[0036] The acidic gas is derived from halogen elements and / or halogen compounds; wherein,

[0037] The halogen element is selected from any one or a combination of two or more of fluorine, chlorine, bromine and iodine, preferably chlorine;

[0038] The halogen compound is selected from any one of hydrogen fluoride, hydrogen chloride, hydrogen bromide, hydrogen iodide, chlorine fluoride, iodine chloride, iodine bromide, bromine chloride, and an acidic precursor compound, or a combination of two or more thereof, preferably hydrogen chloride; wherein the acidic precursor compound can be decomposed by heat in the alkali activation pore-forming step to produce at least one of hydrogen fluoride, hydrogen chloride, hydrogen bromide, hydrogen iodide, chlorine fluoride, iodine chloride, iodine bromide, and bromine chloride.

[0039] 10. A method for preparing a bio-based spherical silicon-carbon negative electrode material, using the bio-based spherical porous carbon prepared by the method for preparing a bio-based spherical porous carbon according to any one of claims 1 to 9, comprising:

[0040] Silicon vapor deposition step: introducing silicon source gas under a protective atmosphere to deposit silicon on the bio-based spherical porous carbon to obtain bio-based spherical porous carbon with nano-silicon deposition;

[0041] Carbon gas phase coating step: introducing carbon source gas under a protective atmosphere to carbon coat the bio-based spherical porous carbon deposited with nano-silicon to obtain the bio-based spherical silicon-carbon negative electrode material.

[0042] 11. The preparation method according to item 10, wherein:

[0043] In the silicon vapor deposition step, the silicon vapor deposition temperature is 450-650° C., preferably 500-550° C.; and / or,

[0044] In the carbon vapor coating step, the carbon coating temperature is 450-700°C, preferably 500-650°C.

[0045] 12. The preparation method according to item 11, wherein:

[0046] The silicon vapor deposition step is carried out in a deposition fluidized bed;

[0047] The silicon source gas introduced under protective atmosphere is:

[0048] A mixed gas of the protective atmosphere gas and the silicon source gas is introduced from the bottom of the deposition fluidized bed; the volume ratio of the protective atmosphere gas to the silicon source gas in the mixed gas is 10:(0.1-10).

[0049] 13. The preparation method according to item 11, wherein:

[0050] The carbon vapor coating step is carried out in a deposition fluidized bed;

[0051] The carbon source gas introduced under protective atmosphere is:

[0052] A mixed gas of the protective atmosphere gas and the carbon source gas is introduced from the bottom of the deposition fluidized bed; the volume ratio of the protective atmosphere gas to the carbon source gas in the mixed gas is 10:(0.1-10).

[0053] 14. The preparation method according to item 10, wherein:

[0054] The silicon source gas is selected from silane and / or chlorosilane; and / or,

[0055] The carbon source gas is selected from one or a combination of two or more of alkanes, alkenes, alkynes and carbon oxides.

[0056] 15. A battery comprising:

[0057] A bio-based spherical silicon-carbon negative electrode material prepared by any method for preparing a bio-based spherical silicon-carbon negative electrode material in items 10 to 14.

[0058] Through the preparation method of the above-mentioned bio-based spherical porous carbon provided by the present application, it is possible to obtain bio-based spherical porous carbon with the characteristics of suitable pore size, uniform pore size, regular spherical shape (good fluidity), single particle strength, etc., which improves and expands the application range of papermaking black liquor, turns waste into treasure, and increases the added value of papermaking black liquor. In addition, the preparation method of the bio-based spherical silicon-carbon negative electrode material of the present application is based on the above-mentioned bio-based spherical porous carbon, and further performs silicon vapor deposition and carbon vapor coating, so as to obtain a bio-based spherical silicon-carbon negative electrode material. The bio-based spherical silicon-carbon negative electrode material has excellent effects such as lower resistivity and stronger restriction ability of internal silicon embedded lithium expansion, so that it can be used to obtain a battery with better performance.

[0059] The above description is only an overview of the technical solution of the present application. In order to make the technical means of the present application clearer and to enable those skilled in the art to implement it according to the contents of the specification, and to make the above and other purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are exemplified below. BRIEF DESCRIPTION OF THE DRAWINGS

[0060] Figure 1 : SEM image of the intermediate porous carbon of Example 1;

[0061] Figure 2 : SEM image of the intermediate porous carbon of Example 2;

[0062] Figure 3 : SEM image of the intermediate porous carbon of Example 3;

[0063] Figure 4 : SEM image of the intermediate porous carbon of Example 4;

[0064] Figure 5 : SEM image of the intermediate porous carbon of Example 5;

[0065] Figure 6 : SEM image of the intermediate porous carbon of Example 6;

[0066] Figure 7 : Electron micrograph of the product obtained in the precursor synthesis step of Comparative Example 1;

[0067] Figure 8 : Electron micrograph of the product obtained in the precursor synthesis step of Comparative Example 2;

[0068] Fig. 9 : Electron micrograph of the product obtained in the precursor synthesis step of Comparative Example 3;

[0069] Fig.10 : Electron micrograph of the product obtained in the precursor synthesis step of Comparative Example 4;

[0070] Fig.11 : Electron micrograph of the product obtained in the precursor synthesis step of Comparative Example 5;

[0071] Fig.12 : Electron micrograph of the product obtained in the precursor synthesis step of Comparative Example 6;

[0072] Fig.13 : Electron microscopy image of commercially available coconut shell-based porous carbon of Comparative Example 7;

[0073] Fig.14 : SEM image of commercially available pitch-based porous carbon of Comparative Example 8. DETAILED DESCRIPTION

[0074] The best mode of the present invention will be shown and described below. Unless otherwise defined, all terms and scientific and technical terms used in this application have the same meaning as those skilled in the art to which the present invention belongs. In the event of inconsistency, the present application (including definitions) takes precedence.

[0075] Definitions of terms particularly used in this specification and / or basic technical contents are described below as appropriate.

[0076] In this application, "papermaking black liquor" refers to the wastewater produced by the alkali (caustic soda) pulping process in the papermaking industry, which contains a large amount of lignin, hemicellulose, pigments, pentoses, nitrogen, phosphorus, potassium and other dissolutions. Since the wastewater is dark brown, it is called papermaking black liquor. The straw and other raw materials used for papermaking contain substances such as cellulose, lignin and hemicellulose. Only cellulose (about 40%) is used for papermaking, while about 25% of lignin and about 28% of hemicellulose, as well as pigments, pentoses, nitrogen, phosphorus, potassium, etc. are discarded with the papermaking black liquor. Because papermaking black liquor contains a large amount of suspended solids, organic pollutants and toxic substances, direct discharge into water bodies will cause serious pollution. Its main hazards are: papermaking wastewater containing a large amount of fiber, pigment and inorganic salt will make the water black and have a special stench; the biochemical oxygen demand (BOD) of papermaking black liquor containing high concentration of organic pollutants can be as high as 5000-40000g / L, which will consume a large amount of dissolved oxygen in the water and affect the water quality; the large amount of alkaline substances in papermaking black liquor will cause the pH value of the water to rise sharply and destroy the balance of the water environment.

[0077] In this application, "drying" refers to evaporating water, and "dehydration" refers to removing crystal water in the structure of alkali salts, etc. at high temperature.

[0078] In the present application, "alkaline pore former" refers to an additive that forms a pore structure by adding alkaline substances that can be decomposed or burned off at high temperature or under specific conditions during the preparation of the material, and specific examples include sodium hydroxide, potassium hydroxide, sodium carbonate, potassium carbonate, etc. For the present application, the "alkaline pore former" contained in the "papermaking black liquor" generally includes sodium hydroxide, that is, the "alkaline pore former" rich in the "bio-based microspheres" themselves generally includes sodium hydroxide.

[0079] In the present application, "protective atmosphere" refers to the use of nitrogen and / or rare gases for protection. Among them, those skilled in the art know that rare gases can be listed, for example, helium (He), neon (Ne), argon (Ar), krypton (Kr), xenon (Xe), etc. From an economic point of view, the present application preferably uses nitrogen as the gas of the protective atmosphere.

[0080] In this application, the "sol-gel method" refers to using compounds containing highly chemically active components as precursors, uniformly mixing these raw materials in a liquid phase, and carrying out hydrolysis and condensation chemical reactions. Under a specific solvent system, the precursor forms a gel with a three-dimensional network structure, and agglomerates into spheres under the action of reverse phase to form gel microspheres.

[0081] In the present application, "activated fluidized bed" refers to a low-speed fluidized bed, in which a high-speed gas flow is introduced into the gas distributor at the bottom of the fluidized bed, so that the solid particles enter a fluidized state and are fully contacted with the gas.

[0082] In the present application, "sedimented fluidized bed" refers to a low-speed stirred fluidized bed, in which a high-speed gas flow is introduced through a gas distributor at the bottom of the fluidized bed, and the dispersion effect of the stirring paddles at the bottom causes the solid particles to enter a fluidized state and come into full contact with the gas.

[0083] The following embodiments are provided to better understand the present invention, and the scope of the present application should not be limited to the following description. Therefore, it is obvious that those skilled in the art can refer to the description in this specification and appropriately change within the scope of the present invention. In addition, the following embodiments of the present invention can also be used alone or in combination.

[0084] In one aspect of the present application, a method for preparing bio-based spherical porous carbon is provided, comprising: a precursor synthesis step: adding a crosslinking agent and a dispersant to papermaking black liquor, and preparing a slurry containing bio-based microspheres by a sol-gel method, wherein the papermaking black liquor is papermaking black liquor produced by alkaline papermaking; a drying and dehydration step: drying and dehydrating the slurry under a protective atmosphere to obtain dried and dehydrated bio-based microspheres; an alkali activation pore-forming step: under a protective atmosphere and at an activation temperature, alkali-activating the dried and dehydrated bio-based microspheres using the alkaline pore-forming agent rich in the microspheres; and a gas phase deashing step: adding an acidic gas under a protective atmosphere to generate salts from the acidic gas and impurities and gasifying and removing the salts to obtain the bio-based spherical porous carbon.

[0085] If papermaking black liquor cannot be effectively treated and is directly discharged, it will not only seriously pollute the environment but also cause a large amount of waste of resources. The inventors of this application creatively utilize the characteristics of industrial alkaline papermaking black liquor that is rich in biomass and alkaline substances. By adopting the sol-gel method, adding a crosslinking agent and a dispersant, the biomass is polymerized into gel microspheres in an alkaline environment, and further post-processing is performed to obtain bio-based spherical porous carbon with the characteristics of suitable pore size, uniform pore size, regular spherical shape (good fluidity), and single particle strength. The bio-based spherical porous carbon can be further used as an intermediate product as described below for battery negative electrode materials, so as to facilitate the acquisition of battery negative electrode materials with lower resistivity and stronger restriction ability on the internal silicon-embedded lithium expansion of the silicon-carbon negative electrode, thereby improving battery performance, or those skilled in the art can use it in other fields according to its characteristics. At the same time, the technical solution of this embodiment expands the application scope of papermaking black liquor, turns waste into treasure, and increases the added value of papermaking black liquor.

[0086] In one embodiment, the solid content of the papermaking black liquor is 30% to 60% (for example, 30%, 35%, 40%, 45%, 55%, or 60%).

[0087] In one embodiment, the pH of the papermaking black liquor is ≥ 11.0, preferably pH ≥ 12.0.

[0088] In one embodiment, the Na content of the papermaking black liquor is 200,000-400,000 ppm (for example, 200,000 ppm, 250,000 ppm, 300,000 ppm, 350,000 ppm, 400,000 ppm), preferably, the Na content is 230,000-250,000 ppm.

[0089] In one embodiment, the cross-linking agent is selected from any one of toluene, phenol, resorcinol, formaldehyde, paraformaldehyde, hexamethylenetetramine, and azobisisobutyl cyanide, or a combination of two or more thereof; preferably, the mass of the cross-linking agent added is 1 to 20% of the mass of the papermaking black liquor (for example, it can be 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%).

[0090] In one embodiment, the dispersant is selected from one or a combination of two or more of gelatin, polyvinyl alcohol, polyethylene glycol, white oil, polyvinyl pyrrolidone, sodium polyacrylate, and sorbitan oleate; preferably, the mass of the dispersant added is 0.1-20% of the mass of papermaking black liquor (for example, it can be 0.1%, 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%).

[0091] In one embodiment, the precursor synthesis step is carried out in a closed reactor; the heating temperature is 170-190°C (for example, it can be 170°C, 172°C, 174°C, 176°C, 178°C, 180°C, 182°C, 184°C, 186°C, 188°C, 190°C), preferably 175-185°C; the heating time is ≥18h, preferably 22-24h; the particle size distribution Dv50 of the obtained spherical particles is between 3 and 15μm (such as it can be 3μm, 5μm, 7μm, 9μm, 11μm, 13μm, 15μm), preferably 5-9μm. At present, the particle size distribution of graphite in the negative electrode of various specifications of battery cells is 5-9μm. Therefore, when spherical particles with the preferred particle size distribution range (5-9μm) are used as silicon-carbon particles for compound graphite, the particle size distribution is similar to that of graphite particles, and it is easier to directly introduce them into the existing production system. If the particles are too large, scratches are easily generated after the electrode is coated, which is not conducive to the yield. If the particles are too small, fine powder will agglomerate, which is not conducive to homogenization.

[0092] In one embodiment, the drying and dehydration step is carried out in an activated fluidized bed; the drying and dehydration step includes a drying sub-step and a dehydration sub-step carried out after the drying sub-step; wherein, in the drying sub-step, the slurry is sprayed into the activated fluidized bed through a two-fluid atomizing nozzle under a protective atmosphere; the drying temperature is 100-150°C (for example, it can be 100°C, 110°C, 120°C, 130°C, 140°C, 150°C), preferably 110-120°C; the slurry is fully The drying time after the part enters the activated fluidized bed is 0.5 to 6 hours (for example, it can be 0.5 hours, 1 hour, 2 hours, 3 hours, 4 hours, 5 hours, 6 hours); the dehydration temperature of the dehydration sub-step is 200 to 800°C (for example, it can be 200°C, 300°C, 400°C, 500°C, 600°C, 700°C, 800°C), preferably 300 to 600°C; the dehydration time is 0.5 to 6 hours (for example, it can be 0.5 hours, 1 hour, 2 hours, 3 hours, 4 hours, 5 hours, 6 hours). Regarding the flow rate of the protective atmosphere gas in this step, those skilled in the art can set it specifically according to the situation. In this embodiment, the linear velocity of the protective atmosphere gas is 0.03 to 0.1 m / s, preferably 0.04 to 0.07 m / s.

[0093] In one embodiment, the alkali activation pore-forming step is carried out in an activated fluidized bed; the activation temperature is set to 600-1100°C (for example, it can be 600°C, 700°C, 800°C, 900°C, 1000°C, 1100°C), preferably 750-950°C; the activation time is 0.5-24h (for example, it can be 0.5h, 1h, 2h, 4h, 6h, 8h, 10h, 12h, 14h, 16h, 18h, 20h, 22h, 24h).

[0094] In one embodiment, in the alkali-activated pore-forming step, an inert gas is continuously introduced into the protective atmosphere from the bottom of the gas-activated fluidized bed. The flow rate of the protective atmosphere gas in this step can be specifically set by those skilled in the art according to the situation. In this embodiment, the linear velocity of the protective atmosphere gas is 0.03 to 0.1 m / s, preferably 0.04 to 0.07 m / s.

[0095] In one embodiment, the gas phase deashing step is carried out in an activated fluidized bed; the gas phase deashing temperature is 400-1100°C (for example, it can be 400°C, 500°C, 600°C, 700°C, 800°C, 900°C, 1000°C, 1100°C), preferably 650-950°C; the deashing time is 0.5-6h (for example, it can be 0.5h, 1h, 2h, 3h, 4h, 5h, 6h).

[0096] In one embodiment, the acidic gas comes from a halogen element and / or a halogen compound; wherein the halogen element is selected from any one or a combination of two or more of fluorine, chlorine, bromine and iodine elements, preferably chlorine; the halogen compound is selected from any one or a combination of two or more of hydrogen fluoride, hydrogen chloride, hydrogen bromide, hydrogen iodide, chlorine fluoride, iodine chloride, iodine bromide, bromine chloride, and an acidic precursor compound, preferably hydrogen chloride; wherein the acidic precursor compound can be decomposed by heat in the alkali activation pore-forming step to produce at least one of hydrogen fluoride, hydrogen chloride, hydrogen bromide, hydrogen iodide, chlorine fluoride, iodine chloride, iodine bromide, and bromine chloride.

[0097] In one aspect of the present application, a method for preparing a bio-based spherical silicon-carbon negative electrode material is provided, which uses the bio-based spherical porous carbon prepared by any of the above-mentioned embodiments, including: a silicon vapor deposition step: introducing a silicon source gas under a protective atmosphere, and performing silicon deposition on the bio-based spherical porous carbon to obtain a bio-based spherical porous carbon with nano-silicon deposition; a carbon vapor coating step: introducing a carbon source gas under a protective atmosphere, and performing carbon coating on the bio-based spherical porous carbon with nano-silicon deposition to obtain the bio-based spherical silicon-carbon negative electrode material.

[0098] In this embodiment, silicon vapor deposition and carbon vapor coating are further performed on the basis of the bio-based spherical porous carbon provided in the above embodiments, so as to obtain a bio-based spherical silicon-carbon negative electrode material. Since the bio-based spherical porous carbon obtained in the above embodiments has the characteristics of suitable pore size, uniform pore size, regular spherical shape (good fluidity), single particle strength, etc., the bio-based spherical silicon-carbon negative electrode material obtained in this embodiment has excellent effects such as lower resistivity and stronger restriction ability of internal silicon embedded lithium expansion, so that it can be used to obtain a battery with better performance.

[0099] In one embodiment, in the silicon vapor deposition step, the silicon vapor deposition temperature is 450-650°C (eg, 450°C, 500°C, 550°C, 600°C, 650°C), preferably 500-550°C.

[0100] In one embodiment, in the carbon vapor coating step, the carbon coating temperature is 450-700°C (eg, 450°C, 500°C, 550°C, 600°C, 650°C, 700°C), preferably 500-650°C.

[0101] In one embodiment, the silicon vapor deposition step is carried out in a fluidized bed; the silicon source gas is introduced under a protective atmosphere by introducing a mixed gas of the protective atmosphere gas and the silicon source gas from the bottom of the fluidized bed; the volume ratio of the protective atmosphere gas and the silicon source gas in the mixed gas is 10:(0.1-10) (for example, it can be 10:01, 10:0.5, 10:1, 10:2, 10:3, 10:4, 10:5, 10:6, 10:7, 10:8, 10:9, 10:10). Regarding the flow rate of the mixed gas, those skilled in the art can set it specifically according to the situation. In this embodiment, the linear velocity of the mixed gas is 0.03-0.1 m / s, preferably 0.04-0.07 m / s.

[0102] In one embodiment, the carbon gas phase coating step is carried out in a fluidized bed; the carbon source gas is introduced under a protective atmosphere by introducing a mixed gas of the protective atmosphere gas and the carbon source gas from the bottom of the fluidized bed; the volume ratio of the protective atmosphere gas and the carbon source gas in the mixed gas is 10:(0.1-10) (for example, it can be 10:01, 10:0.5, 10:1, 10:2, 10:3, 10:4, 10:5, 10:6, 10:7, 10:8, 10:9, 10:10). Regarding the flow rate of the mixed gas, those skilled in the art can set it specifically according to the situation. In this embodiment, the linear velocity of the mixed gas is 0.03-0.1 m / s, preferably 0.04-0.07 m / s.

[0103] In one embodiment, the silicon source gas is selected from silane and / or chlorosilane.

[0104] In one embodiment, the carbon source gas is selected from one or a combination of two or more of alkanes, alkenes, alkynes, and carbon oxides.

[0105] In one aspect of the present application, a battery is provided, comprising: a bio-based spherical silicon-carbon negative electrode material prepared by any of the above-mentioned methods for preparing bio-based spherical silicon-carbon negative electrode materials.

[0106] Example

[0107] The experimental methods used below are conventional methods unless otherwise specified.

[0108] Unless otherwise specified, the materials and reagents used below can be obtained from commercial sources.

[0109] Unless otherwise specified, the papermaking black liquor used in the following examples and comparative examples is all from the papermaking black liquor produced by the alkaline papermaking process of Daqing Shengquan Group.

[0110] In the following examples and comparative examples, pH was measured using a Mettler FE28 benchtop pH meter, and Na content was measured using an American Thermo Fisher iCAPPRO XP Duo inductively coupled plasma emission spectrometer (ICP).

[0111] The bio-based spherical porous carbons of Examples 1 to 6 and Comparative Examples 1 to 6 shown in Table 1 below were prepared by the following method.

[0112] Crosslinker A

[0113] A-1: Phenol

[0114] A-2: Formaldehyde

[0115] A-3: Hexamethylenetetramine

[0116] A-4: Paraformaldehyde

[0117] A-5: Resorcinol

[0118] Dispersant B

[0119] B-1: Sorbitan Oleate

[0120] B-2: White oil

[0121] B-3: Polyvinyl alcohol

[0122] B-4: Polyvinyl pyrrolidone

[0123] B-5: Gelatin

[0124] Example 1

[0125] Add papermaking black liquor (230kg, solid content 30%, pH=12, Na content 240000ppm), crosslinking agent (8kg phenol, 2kg formaldehyde, 10kg hexamethylenetetramine), dispersant (1kg sorbitan oleate, 2kg white oil) into a high-pressure jacket reactor, stir at room temperature for 2h, then heat the reactor to 180℃ and stir slowly at this temperature for 24h. (Precursor synthesis step)

[0126] The slurry is cooled to 120°C, and then pressure is used to transport the slurry to the activated fluidized bed heated to 110°C. It is sprayed into the fluidized bed cavity under nitrogen protection through a two-fluid atomizing nozzle. After all the slurry is sprayed into the fluidized bed, the powder is dried at a constant temperature of 110°C for 6 hours. The activated fluidized bed is then heated to 500°C at a rate of 8°C / min and kept at a constant temperature for 4 hours to dehydrate the powder. During drying and dehydration, nitrogen is continuously introduced into the bottom of the activated fluidized bed to purge the powder. (Drying and dehydration steps)

[0127] When dehydration is completed, the temperature of the activated fluidized bed is raised to 750°C at a rate of 2°C / min and maintained for 12 hours. At the same time, nitrogen is introduced into the bottom of the activated fluidized bed to perform alkali activation on the powder. (Alkali activation pore-forming step)

[0128] After the alkali activation is completed, the temperature is raised to 900°C at 2°C / min, and a mixed gas of HCl and nitrogen is introduced into the bottom of the activated fluidized bed. The volume ratio of HCl and nitrogen is 1.5:8.5. After maintaining for 4 hours, the gas phase deashing is completed. After the gas phase deashing is completed, the heating of the activated fluidized bed is turned off to reduce the temperature in the activated fluidized bed to below 100°C, and the intermediate bio-based spherical porous carbon is obtained. (Gas phase deashing step)

[0129] Bio-based spherical porous carbon is transferred from the activated fluidized bed to the deposited fluidized bed by gas transport. The fluidized bed is heated under the protection of a nitrogen atmosphere. When the fluidized bed is heated to 520°C, the temperature is kept constant. A mixed gas of monosilane and nitrogen is introduced from the bottom of the fluidized bed. The volume ratio of monosilane to nitrogen is 3:13. Silicon vapor deposition is performed. After 400 minutes, the introduction of monosilane is stopped. (Silicon vapor deposition step)

[0130] The fluidized bed was heated to 600°C under a nitrogen atmosphere, and the temperature was kept constant. A mixed gas of acetylene and nitrogen was introduced, and the volume ratio of acetylene to nitrogen was 3:13, and carbon vapor coating was performed. After 360 minutes, the introduction of acetylene was stopped, and the fluidized bed heating was turned off. The fluidized bed was cooled down under a nitrogen atmosphere. When the fluidized bed temperature dropped to below 100°C, the reactor was discharged to obtain a spherical silicon-carbon negative electrode material prepared from bio-based spherical porous carbon. (Carbon vapor coating step)

[0131] Compared with Example 1, the differences between other examples and comparative examples for preparing bio-based spherical silicon-carbon negative electrode materials are only the types of reagents, mass fractions, and reaction conditions used in the precursor synthesis step shown in Table 1. In addition, since comparative examples 1 to 6 obtain block polymers rather than bio-based microspheres in the precursor synthesis step, comparative examples 1 to 6 only perform the precursor synthesis step and do not perform subsequent steps. The preparation conditions of Examples 1 to 6 and Comparative Examples 1 to 6 are shown in Table 1.

[0132] Table 1 Process parameters of precursor synthesis steps

[0133]

[0134] Comparative Example 7 (Preparation of silicon-carbon negative electrode material using coconut shell-based porous carbon as raw material)

[0135] Commercially available coconut shell-based porous carbon (parameters are shown in Tables 2 and 3) was fed into the deposition fluidized bed, and the fluidized bed was heated under the protection of a nitrogen atmosphere. When the fluidized bed was heated to 520°C, the temperature was kept constant, and a mixed gas of monosilane and nitrogen was introduced from the bottom of the fluidized bed. The volume ratio of monosilane to nitrogen was 3:13, and silicon vapor deposition was performed. After 400 minutes, the introduction of monosilane was stopped. (Silicon vapor deposition step)

[0136] The fluidized bed was heated to 600°C under a nitrogen atmosphere, and the temperature was kept constant. A mixed gas of acetylene and nitrogen was introduced, and the volume ratio of acetylene to nitrogen was 3:13. Carbon vapor coating was performed. After 360 minutes, the introduction of acetylene was stopped, and the fluidized bed heating was turned off. The fluidized bed was cooled down under a nitrogen atmosphere. When the fluidized bed temperature dropped below 100°C, the reactor was discharged to obtain a spherical silicon-carbon negative electrode material prepared from coconut shell-based porous carbon. (Carbon vapor coating step)

[0137] Comparative Example 8 (Preparation of Silicon Carbon Anode Material Using Pitch-Based Porous Carbon as Raw Material)

[0138] Commercially available asphalt-based porous carbon (parameters are shown in Tables 2 and 3) was fed into the deposition fluidized bed, and the fluidized bed was heated under the protection of a nitrogen atmosphere. When the fluidized bed was heated to 520°C, the temperature was kept constant, and a mixed gas of monosilane and nitrogen was introduced from the bottom of the fluidized bed. The volume ratio of monosilane to nitrogen was 3:13, and silicon vapor deposition was performed. After 400 minutes, the introduction of monosilane was stopped. (Silicon vapor deposition steps)

[0139] The fluidized bed was heated to 600°C under a nitrogen atmosphere, and the temperature was kept constant. A mixed gas of acetylene and nitrogen was introduced, and the volume ratio of acetylene to nitrogen was 3:13. Carbon vapor coating was performed. After 360 minutes, the introduction of acetylene was stopped, and the fluidized bed heating was turned off. The fluidized bed was cooled down under a nitrogen atmosphere. When the fluidized bed temperature dropped below 100°C, the reactor was discharged to obtain a spherical silicon-carbon negative electrode material prepared by asphalt-based porous carbon. (Carbon vapor coating step)

[0140] Test example

[0141] Porous carbon particle size detection and electron microscope image

[0142] In the preparation process of the above Examples 1 to 6, the particle size of the intermediate bio-based spherical porous carbon was detected, and the particle size of the commercial coconut shell-based porous carbon of Comparative Example 7 and the commercial asphalt-based porous carbon of Comparative Example 8 was detected. The particle sizes were measured by Malvern Laser Particle Sizer Mastersizer 3000E. The test results are shown in Table 2. In addition, the intermediate products obtained in Examples 1 to 6 and Comparative Examples 1 to 6, the commercial coconut shell-based porous carbon of Comparative Example 7, and the commercial asphalt-based porous carbon of Comparative Example 8 were analyzed by field emission scanning electron microscopy. The test results are shown in Table 2. Figure 1 to Figure 14 Among them, Examples 1 to 6 are electron microscopic photographs of the intermediate porous carbon, and Comparative Examples 1 to 6 are electron microscopic photographs of the products (block polymers) obtained in the precursor synthesis step.

[0143] Table 2 Porous carbon particle size

[0144]

[0145] Through Table 1, Table 2 and Figures 1 to 12 It can be seen that in the precursor synthesis step, cross-linking agent, dispersant, reaction temperature, time, etc. play an important role in the reaction results.

[0146] For Examples 1 to 6, see Table 1, Figure 1 to Figure 6 It can be seen that it is possible to synthesize bio-based microspheres with suitable particle size (no need for further crushing and grading and screening) and relatively perfect spherical shape.

[0147] For Comparative Examples 1 to 6, see Table 1, Figure 7 to Figure 12 . Comparative Example 1 did not use a cross-linking agent and a dispersant, and directly carried out polymerization. Comparative Examples 2-3 only used one of the cross-linking agent or the dispersant. The lack of a cross-linking agent or a dispersant would cause the formed spherical precursors to stick to each other and could not be dispersed in a single particle state. They could not be used normally without additional crushing. Comparative Examples 4-5 changed the polymerization temperature conditions. Too low a reaction temperature would result in the failure to achieve polymerization, and too high a reaction temperature would result in too fast a polymerization rate to form blocky resin. Comparative Example 6 used black liquor with a higher solid content concentration, and the liquid portion of the papermaking black liquor acted as a partial solvent. In Comparative Example 6, the solid content of the papermaking black liquor was too high, resulting in too little actual solvent, which resulted in the synthetic substance being unable to be evenly dispersed in the solvent and polymerized into spheres, and the polymer was a blocky polymer.

[0148] Porous carbon, negative electrode materials and battery performance testing

[0149] The applicant tested the porous carbon and battery negative electrode materials of Example 4, Comparative Example 7 and Comparative Example 8. The test results are detailed in Table 3 below.

[0150] In order to detect the performance of the negative electrode material, button batteries were prepared and the battery performance was tested. The preparation method of the button battery is as follows: the silicon-carbon negative electrode material: SP: CMC: LA136D is prepared into a slurry in a ratio of 75:10:2.5:12.5 (SP (Supercarbon) is a conductive agent, CMC is carboxymethyl cellulose (CMC 2200), LA136D is an aqueous silicon-carbon negative electrode binder, and the materials are commonly used in the production of button batteries). The material is homogenized in an Intet ITI-300SS vacuum stirring and degassing machine, and then coated on a 9μm copper foil using a coating machine with a coating thickness of 120μm. After the foil coated with the slurry is dried, it is cut into The circular pole piece is made of lithium sheet, circular pole piece, ceramic PVDF diaphragm and LB-137 to assemble CR2032 battery. The specifications of lithium sheet are: Membrane specifications: base membrane 9μm, PVDF coating 3μm, ceramic layer 1μm, electrolyte specifications: 1M LiPF6 in DMC:EC:EMC=1:1:1Vol%with 5%FEC,1%VC, dosage: 60μL.

[0151] Among them, Micromeritics' ASAP2460 multi-station extended fully automatic specific surface and porosity analyzer was used to detect the pore volume, specific surface area, and average pore size of porous carbon; Tanggula comprehensive test powder instrument (PT-Pro) was used to test the collapse angle, difference angle, dispersion, and fluidity index of porous carbon; Japan's Shimadzu MCT-210 micro compression testing machine was used to determine the single particle strength of silicon-carbon negative electrode materials; and Steel Research Institute Nano-carbon Carbon Sulfur Instrument (3500) was used to determine the carbon content of the negative electrode material.

[0152] Table 3: Test results of porous carbon and battery negative electrode materials

[0153]

[0154] Comparative Examples 7 and 8 both use block-shaped porous carbon, and their pore volume and particle size distribution are similar to those of the spherical porous carbon in Example 4. The difference between the two is the different particle shapes. Therefore, the effect of particle fluidity on the silicon deposition effect can be verified. Compared with the porous carbon in Comparative Examples 7 and 8 of the prior art, the porous carbon prepared in Example 4 of the present application is significantly higher in fluidity than the porous carbon in Comparative Examples 7 and 8, which is mainly reflected in a larger collapse angle, a larger difference angle, and a higher statistical fluidity index. Therefore, when silicon vapor deposition is carried out in a fluidized bed, the fluidization state of the porous carbon is It will be significantly stronger than the porous carbon of Examples 7 and 8 of the prior art, with better gas-solid contact, and better silicon deposition under the same conditions; the porous carbon of Example 4 of the present application is similar to the porous carbon of Examples 7 and 8 in pore volume, but has a smaller average pore size. After silicon is deposited and carbon coated under the same conditions, the obtained sample powder has a smaller resistivity, indicating that compared with Examples 7 and 8, less silicon is deposited on the outer surface of the porous carbon, resulting in lower powder resistance, and the 1.5V reversible capacity is higher, indicating that during the silicon deposition stage, the porous carbon has a higher adsorption efficiency for monosilane. In the single particle strength test of the silicon-carbon negative electrode prepared in Example 4, the average value of the deformation pressure Cs is 922.43Mpa, which is significantly higher than the average Cs of Examples 7 and 8. The silicon-carbon negative electrode material prepared by the bio-based spherical porous carbon of the technical solution of the present application has a higher single particle strength, and has a high binding force in terms of silicon expansion after lithium insertion, which can effectively alleviate the reduction in battery cycle life caused by silicon expansion. In addition, the powder resistivity of the silicon-carbon negative electrode materials prepared in Comparative Examples 7 and 8 is too high, making it difficult to obtain qualified battery cell products. The silicon-carbon negative electrode material prepared by the technical solution of the present application (such as Example 4) can significantly reduce the powder resistivity.

Claims

1. A method for preparing bio-based spherical porous carbon, comprising: Precursor synthesis step: adding a crosslinking agent and a dispersant to papermaking black liquor, and preparing a slurry containing bio-based microspheres by a sol-gel method, wherein the papermaking black liquor is papermaking black liquor produced by alkaline papermaking; Drying and dehydrating step: drying and dehydrating the slurry under a protective atmosphere to obtain dried and dehydrated bio-based microspheres; Alkali activation pore-forming step: in a protective atmosphere and at an activation temperature, the dried and dehydrated bio-based microspheres are subjected to alkali activation using the alkaline pore-forming agent that is rich in the microspheres; Gas phase deashing step: adding acidic gas under protective atmosphere, so that the acidic gas and impurities generate salt and are gasified and removed to obtain the bio-based spherical porous carbon.

2. The preparation method according to claim 1, wherein The solid content of the papermaking black liquor is 30% to 60%; The pH of the papermaking black liquor is ≥ 11.0, preferably ≥ 12.0; The Na content of the papermaking black liquor is 200000-400000 ppm, preferably 230000-250000 ppm; The cross-linking agent is selected from any one of toluene, phenol, resorcinol, formaldehyde, paraformaldehyde, hexamethylenetetramine, and azobisisobutyl cyanide, or a combination of two or more thereof; preferably, the mass of the cross-linking agent added is 1 to 20% of the mass of the papermaking black liquor; and / or, The dispersant is selected from one or a combination of two or more of gelatin, polyvinyl alcohol, polyethylene glycol, white oil, polyvinyl pyrrolidone, sodium polyacrylate, and sorbitan oleate; preferably, the mass of the dispersant added is 0.1-20% of the mass of papermaking black liquor.

3. The preparation method according to claim 1, wherein The precursor synthesis step is carried out in a closed reactor; the heating temperature is 170-190° C., preferably 175-185° C.; the heating time is ≥18 h, preferably 22-24 h; and / or, The drying and dehydration step is carried out in an activated fluidized bed; the drying and dehydration step includes a drying sub-step and a dehydration sub-step carried out after the drying sub-step; wherein, in the drying sub-step, the slurry is sprayed into the activated fluidized bed through a two-fluid atomizing nozzle under a protective atmosphere; the drying temperature is 100-150°C, preferably 110-120°C; the drying time after all the slurry enters the activated fluidized bed is 0.5-6h; the dehydration temperature of the dehydration sub-step is 200-800°C, preferably 300-600°C; and the dehydration time is 0.5-6h.

4. The preparation method according to claim 1, wherein The alkali activation pore-forming step is carried out in an activated fluidized bed; the activation temperature is 600-1100° C., preferably 750-950° C.; the activation time is 0.5-24 hours; Preferably, in the alkali-activated pore-forming step, an inert gas of the protective atmosphere is continuously introduced from the bottom of the gas-activated fluidized bed.

5. The preparation method according to claim 1, wherein The gas phase deashing step is carried out in an activated fluidized bed; The gas phase deashing temperature is 400-1100°C, preferably 650-950°C; The decalcification time is 0.5 to 6 hours.

6. The preparation method according to claim 1, wherein The acidic gas is derived from halogen elements and / or halogen compounds; wherein, The halogen element is selected from any one or a combination of two or more of fluorine, chlorine, bromine and iodine, preferably chlorine; The halogen compound is selected from any one of hydrogen fluoride, hydrogen chloride, hydrogen bromide, hydrogen iodide, chlorine fluoride, iodine chloride, iodine bromide, bromine chloride, and an acidic precursor compound, or a combination of two or more thereof, preferably hydrogen chloride; wherein the acidic precursor compound can be decomposed by heat in the alkali activation pore-forming step to produce at least one of hydrogen fluoride, hydrogen chloride, hydrogen bromide, hydrogen iodide, chlorine fluoride, iodine chloride, iodine bromide, and bromine chloride.

7. A method for preparing a bio-based spherical silicon-carbon negative electrode material, using the bio-based spherical porous carbon prepared by the method for preparing a bio-based spherical porous carbon according to any one of claims 1 to 6, comprising: Silicon vapor deposition step: introducing silicon source gas under a protective atmosphere to deposit silicon on the bio-based spherical porous carbon to obtain bio-based spherical porous carbon with nano-silicon deposition; Carbon gas phase coating step: introducing carbon source gas under a protective atmosphere to carbon coat the bio-based spherical porous carbon deposited with nano-silicon to obtain the bio-based spherical silicon-carbon negative electrode material.

8. The preparation method according to claim 7, wherein In the silicon vapor deposition step, the silicon vapor deposition temperature is 450-650° C., preferably 500-550° C.; In the carbon vapor coating step, the carbon coating temperature is 450-700°C, preferably 500-650°C; Preferably, the silicon vapor deposition step is carried out in a deposition fluidized bed; the silicon source gas is introduced under a protective atmosphere by introducing a mixed gas of the protective atmosphere gas and the silicon source gas from the bottom of the deposition fluidized bed; the volume ratio of the protective atmosphere gas to the silicon source gas in the mixed gas is 10:(0.1-10); and / or, Preferably, the carbon vapor coating step is carried out in a deposition fluidized bed; the carbon source gas is introduced under a protective atmosphere: a mixed gas of the protective atmosphere gas and the carbon source gas is introduced from the bottom of the deposition fluidized bed; the volume ratio of the protective atmosphere gas to the carbon source gas in the mixed gas is 10: (0.1~10).

9. The preparation method according to claim 7, wherein: The silicon source gas is selected from silane and / or chlorosilane; and / or, The carbon source gas is selected from one or a combination of two or more of alkanes, alkenes, alkynes and carbon oxides.

10. A battery comprising: A bio-based spherical silicon-carbon negative electrode material prepared by the method for preparing a bio-based spherical silicon-carbon negative electrode material according to any one of claims 7 to 9.

Citation Information

Patent Citations

  • Adhesive prepared from paper making black liquor for forming active carbon

    CN101092550A

  • Comprehensive utilization method of papermaking black liquor

    CN108192543A

  • Method for preparing porous carbon materials from waste black liquor activated by bacteria and application of porous carbon materials

    CN109160505A

  • Nano hydroxyl iron oxide gel composite material as well as preparation method and application thereof

    CN113121758A

  • Method for preparing biochar and organic fertilizer from corn straw and papermaking black liquor

    CN116177527A

Cited By

  • Biomass-derived spherical porous carbon material and preparation method thereof, and silicon-carbon negative electrode material and preparation method thereof

    CN121085268A